Effectiveness of corifollitropin alfa used for ovarian stimulation of poor responder patients - Selman H; Rinaldi L (Dove Medical Press, 2016)
Helmy Selman, Leonardo Rinaldi One Day Medical Center–IVF Unit, Roma, Italy Purpose: To evaluate the efficiency and efficacy of corifollitropin alfa (follicle-stimulating hormone–carboxy terminal peptide) in the treatment of poor responder patients. Methods: A total of 85 poor responder patients with a mean age 40.2±3.9 years entered our assisted fertilization program. The patients were prospectively randomized into two groups based on the ovarian stimulation regimen used: group A (study group) (n=42) received clomiphene citrate and corifollitropin alfa for the first 7 days of stimulation followed by recombinant follicle stimulating hormone (rFSH) in a gonadotropin-releasing hormone antagonist protocol, and group B (control group) (n=43) received clomiphene citrate and a daily injection of rFSH in a gonadotropin-releasing hormone antagonist protocol. We analyzed the stimulation outcome, the number of retrieved oocytes, cleaving embryos, and pregnancy and implantation rates as well. Results: Comparable results were observed between the two groups in terms of demographic data, stimulation outcome, and the number of canceled cycles. There were no differences evident between groups A and B with respect to the number of retrieved oocytes (3.0±0.8 and 2.7±0.7, respectively) and the number of cleaving embryos (1.8±0.6 and 1.7±0.7, respectively). Higher, though not statistically significant, differences were observed in favor of group A compared to group B in terms of pregnancy rate per cycle (19% and 16.3%, respectively), pregnancy rate per transfer (21.6% and 17.9%, respectively), and implantation rate (14.7% and 13.4%, respectively). Also, miscarriage rate was similar between patients treated with corifollitropin alfa and those treated with daily rFSH injection (12.5% and 14.2%, respectively). Conclusion: The results show that ovarian stimulation with corifollitropin alfa appears to be as efficacious and efficient as daily injection rFSH regimen to treat patients with poor ovarian response. Keywords: Long-acting FSH, recombinant FSH, ovarian stimulation, ovarian response, pregnancy